Plasticity of instinct: Interactions of the memory engram with innate behaviour - Conway, Paul Bernard (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2025)
The brain has access to two sources of information to guide behaviour; instinct and memory. While research into these two phenomena is advancing rapidly, much less is known about how they interact with one another. This thesis investigates the interplay between memory and instinct in the brain, using two behavioural models: the innate defensive responses of Mus musculus to visual looming stimuli, and the olfactory responses of Mus musculus and Mus caroli to the odorant trimethylamine (TMA). I demonstrate that innate fear responses to visual looming stimuli are subject to experience-dependent plasticity. This plasticity results in reduced activation of circuitry responsible for driving the behaviour, specifically the superior colliculus (SC) and periaqueductal gray (PAG). Using engram labelling technology, I identify a novel role for the hippocampus in mediating adaptive behavioural responses to visual looming stimuli. Additionally, I show that the TMA response of Mus musculus is influenced by both innate and learned factors, with early life sensory exposure crucial to the development of an appropriate behavioural response. I identify the anterior olfactory nucleus (AON) as a key region involved in processing TMA responses in Mus musculus. Comparative c-Fos-based mapping in Mus caroli reveals divergent neural circuits underlying their instinctive aversion, suggesting a shift in olfactory circuitry accompanying the evolution of attraction in Mus musculus. Together, these findings provide insight into how memory can modify instinctive behaviours and how learning contributes to the development and evolution of instinct. This work advances our understanding of the neural circuits underlying instinct-memory interactions, demonstrating that these two systems are not isolated but are constantly shaping one another to drive adaptive behaviour. Understanding this relationship will advance our understanding of how the brain controls behaviour, the role for learning in this process, and how information is stored in the brain.
APPROVED
Keywords: Instinct; Innate; Memory; Plasticity; Looming; Olfaction; Evolution; Behaviour; Engram